2022
DOI: 10.1177/17470218221076850
|View full text |Cite
|
Sign up to set email alerts
|

The influence of three-dimensional cues on body size judgements

Abstract: Research has shown that body size judgements are frequently biased, or inaccurate. Critically, judgement biases are further exaggerated for individuals with eating disorders, a finding that has been attributed to difficulties integrating body features into a perceptual whole. However, current understanding of which body features are integrated when judging body size is lacking. In this study, we examine whether individuals integrate three-dimensional (3D) cues to body volume when making body size judgements. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…This study ensured that on each trial, each body varied in appearance, clothing and overall lighting. Furthermore, in our study, our CG stimuli have the advantage of including stereoscopic (e.g., three-dimensional) cues, which provide further realism and ecological validity, relative to 2D CG stimuli used in previous studies (Turnbull et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This study ensured that on each trial, each body varied in appearance, clothing and overall lighting. Furthermore, in our study, our CG stimuli have the advantage of including stereoscopic (e.g., three-dimensional) cues, which provide further realism and ecological validity, relative to 2D CG stimuli used in previous studies (Turnbull et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…This is a potentially important consideration given research showing that 3D cues can enhance and/or alter sensitivity to objects and object recognition (Bennett and Vuong, 2006;Burke et al, 2007;Bell et al, 2013;Caziot and Backus, 2015). In addition, Turnbull et al (2022) found that 3D cues influence body size judgements by providing viewers with increased stimulus certainty (e.g., addition of volumetric of lower stomach and bust regions). Furthermore, from an ecological perspective, the bodies that we often see in real life are surrounded by other people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations